Madeleine's ghost - Girardi, Robert (Delacorte Press, 1995)
Ned Conti is a young historian struggling to piece together the miraculous past of a Brooklyn nun for a tiny stipend, while, at night, he grapples with the paranormal phenomena that have recently seized his rent-controlled apartment: furniture set askew, strange light haunting the bedroom, rocks appearing mysteriously in midair to pummel the floor. His only refuge is the F train and its connection to long Manhattan nights in East Village bars that he visits with his forlorn and eccentric friends. As the summer grows hotter and his apartment more threatening, a baffled but tolerant Ned sets out to uncover the secret behind the angry spirit and, in so doing, is drawn irretrievably into a world of desire and fate ... where all around him lingers the dark dream of New Orleans, a place of magical disaster. Ten years before, he fled the Crescent City, never to return, when Antoinette, his true love, ended their brief but urgent affair. Now he's going back, returning to the past that has haunted him for a decade.